Begomovirus disease of pumpkin crop in India and its management strategies possibility: a review - Kushvaha, Ram Prasad; Kushwaha, Chitra; Snehi, Sunil Kumar (Journal of Scientific Agriculture, 2024)
Pumpkin is an important commercial crop grown worldwide in tropical and subtropical regions. The whitefly-transmitted Pumpkin yellow vein mosaic disease seriously threatens pumpkin cultivation worldwide. The advent of transgenic technology in the 1980s revolutionized the possibilities for introducing virus resistance into agriculturally important plant species. It offered a powerful tool to enhance crop protection and provided a pathway to potentially unlimited sources of resistance against viral diseases. The ongoing research and development in this field continue to explore and refine conventional and non-conventional approaches for effective virus management in agriculture crops. This review focuses on developing transgenic resistance against begomoviruses and discusses possible management strategies to address these challenges.